Environmental Stress Selects for Innovations That Drive Vibrio Symbiont Diversity - Soto, William; Nishiguchi, Michele K. (Frontiers in Ecology and Evolution, 2021)
Symbiotic bacteria in the Vibrionaceae are a dynamic group of -Proteobacteria that are commonly found throughout the world. Although they primarily are free-living in the environment, they can be commonly found associated with various Eukarya, either as beneficial or pathogenic symbionts. Interestingly, this dual lifestyle (free-living or in symbiosis) enables the bacteria to have enormous ecological breadth, where they can accommodate a variety of stresses in both stages. Here, we discuss some of the most common stressors that Vibrio bacteria encounter when in their free-living state or in associated with an animal host, and how some of the mechanisms that are used to cope with these stressors can be used as an evolutionary advantage that increases their diversity both in the environment and within their specific hosts.